2017
DOI: 10.1080/10253866.2017.1367680
|View full text |Cite
|
Sign up to set email alerts
|

Graves, gifts, and the bereaved consumer: a restorative perspective of gift exchange

Abstract: When a gifting relationship is disrupted by death, why might a living consumer continue to invest in it? Consumer spending on deceased loved ones does not end with the funeral. Given the embodying power of a physical gravesite, this article examines the practice of gift giving to the deceased in the context of American cemeteries. We employ a longitudinal approach, in which 180 cemetery gravesites were photographed. The photographic data are coupled with a netnography of grief and bereavement communities. Find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…Research in the field of bereavement studies has found that artefacts associated with deceased loved ones, defined here as "cherished…special possessions which are treasured independent of their exchange value" and which have been invested with "private or personal meanings" by the bereaved (Curasi et. al., 2004:609), can support the management of strong feelings of grief after loss (Castle and Phillips 2003;Drenton et. al., 2017;Gibson, 2004;Goldstein et.…”
Section: The Role Of Artefacts In Coping With Lossmentioning
confidence: 99%
“…Research in the field of bereavement studies has found that artefacts associated with deceased loved ones, defined here as "cherished…special possessions which are treasured independent of their exchange value" and which have been invested with "private or personal meanings" by the bereaved (Curasi et. al., 2004:609), can support the management of strong feelings of grief after loss (Castle and Phillips 2003;Drenton et. al., 2017;Gibson, 2004;Goldstein et.…”
Section: The Role Of Artefacts In Coping With Lossmentioning
confidence: 99%
“…We were able to identify 13 articles with a direct focus on this transition. Examples of liminal transitions identified by our review include other major life changes such as the transition to a new age category (e.g., Cody & Lawlor, 2011), the modification of an important relationship or a person's professional status (e.g., Fernandez et al., 2011; Ulver & Ostberg, 2014), changes such as the death of a loved one that impacts a person's circle of close friends and family members (Drenten et al., 2017), the occurrence of a natural disaster (Baker et al., 2007, Cheung & McColl‐Kennedy, 2015), and the toppling of a political system (Al‐Abdin et al., 2016). These liminal transitions vary in nature, and some are considered more desirable than others (e.g., a promotion vs. a job loss).…”
Section: Overview Of Liminalitymentioning
confidence: 99%
“…Consumer researchers have studied funerals as a rite of passage (Cengiz & Rook, 2016; Gentry et al., 1995; O’Donohoe & Turley, 2006) and from a materialistic perspective of social status signaling and possessions (Bonsu & Belk, 2003; Drenten, McManus, & Labrecque, 2017). From these studies, funerals emerge as an emotionally charged and reflexive consumption context characterized by high stress and often extreme grief (Bonsu & Belk, 2003; O’Donohoe & Turley, 2006).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…People planning funerals feel strong cultural obligations for adherence to cultural traditions and family norms, where funerals constitute a reciprocal and continuing relationship between the deceased and the planner. In a way, the deceased continues to influence consumer decisions after their death (see also Drenten et al., 2017; Gentry et al., 1995).…”
Section: Theoretical Backgroundmentioning
confidence: 99%